Software engineering: principles and practice - Jawadekar, W. S. Wamana S. Jawadekar (New Delhi: Tata McGraw-Hill, 2004)
This book presents an integrated view of the principles and practice of Software Engineering. Extensive coverage of both the approaches to the topic, Systems and Object-Oriented, illustrious examples and case studies, make it an invaluable text for the students learning the subject.
Include appendices, glossary and index
Keywords: Software Engineering -- Principles and Practice